(untitled) (El-Wahat Journal for Research and Studies, 2021)
Educational text is one of the impotant pillars of the educational process , and is also very important for it to go ahead , on consederating that the main action that the educational text has , is to make learning achieves its role , and touches its desires , such as , social , ethical, and educational ones . So, from this point of view ,I want to focus on one of the important fanction of educational text , which is planting the national spirit and make students and teachers atached to their town and nation , by taking the arabic language book for the second year of average , as a model. Keywords: Algerian legal textbook, National textbook, Arabic language book, second year intermediate